Dietary Intake of Riboflavin and Unsaturated Fatty Acid Can Improve the Multi-Domain Cognitive Function in Middle-Aged and Elderly Populations: A 2-Year Prospective Cohort Study - Tao, Lingwei; Liu, Kuo; Chen, Si; Yu, Huiyan; An, Yu; Wang, Ying; Zhang, Xiaona; Wang, Yushan; Qin, Zhongsheng; Xiao, Rong (Frontiers in Aging Neuroscience, 2019)
Objective: This study was aimed to explore the effects of dietary nutrients on cognitive function among the middle-aged and elderly populations. Methods: A prospective cohort study of 1385 middle-aged and elderly people was conducted from January 2014 to December 2017. Dietary nutrients were assessed according to the food frequency questionnaire (FFQ) and China Food Composition Database. Montreal cognitive assessment (MoCA) was used to evaluate the participants’ global cognitive function. Six other neuropsychological measures (auditory verbal learning test-immediate recall (AVLT-IR), auditory verbal learning test-short recall (AVLT-SR), auditory verbal learning test-long recall (AVLT-LR), logical memory test (LMT), digit span forwards (DST-F) and digit span backwards (DST-B)) were used to assess the verbal memory domain and the attention domain by principal component analysis. Multiple linear regressions were conducted to explore associations between nutrients and cognition. Sensitivity analyses were performed to confirm the results. Results: Dietary riboflavin was protective for global cognitive function (β=1.31, 95% CI: 0.26, 2.35) and the verbal memory domain (β=0.37, 95% CI: 0.02, 0.71). Unsaturated fatty acid (USFA) played a protective role in global cognitive function (β=1.15, 95% CI: 0.16, 2.14). The protective effects of riboflavin and USFA on cognitive function were consistent and reliable when different confounders were adjusted during sensitivity analyses. During the follow-up, neuropsychological measure scores revealed a reduced declines in the high riboflavin group (d-MoCA, P=0.025; d-AVLT-IR, P=0.001; d-DST-B, P=0.004 and d-composite score, P=0.004) and the high USFA group (d-AVLT-IR, P=0.007; d-LMT, P=0.032; d-DST-B, P=0.002 and d-composite score, P=0.008). Conclusion: Higher intake of riboflavin and USFA can improve multi-dimensional cognitive functioning in middle-aged and elderly people. These findings were consistent in different models of sensitivity analyses.